Learning places, teaching methods, techniques and materials used in General Studies (Sachunterricht) lesson by teachers in German primary schools’ third grade - BAYSAL, ZELİHA NURDAN (Routledge, 2021)
General Studies (Sachunterricht) lesson, which includes social and science themes because of its interdisciplinary form, takes place in the curriculum of each class level at primary schools in Germany. The aim of this descriptive case study is to examine how the teaching process of third-grade General Studies lesson is run in terms of learning place, teaching methods and techniques, and materials. The participants of it are six teachers of third grade from three different primary schools. The data were collected through classroom observations and interviews with teachers. While analysing the data, the content and the descriptive analysis methods were used. The results indicate that the teachers use classrooms, corridors, the workshop room, the schoolyards, trip fields and sport fields as learning spaces. Some of the teaching methods and techniques used are learning stations, project, class council, field trips, experiments, cooperative learning and teachers choose various teaching materials, depending on the theme. © 2021 ASPE.
Keywords: General Studies; learning place; Sachunterricht; teaching materials; teaching methods and techniques